1993
DOI: 10.1046/j.1469-0705.1993.03020097.x
|View full text |Cite
|
Sign up to set email alerts
|

Trends in sonographic fetal organ visualization

Abstract: In order to assess changes in sonographic visualization over the last 6 years, 7092 second- and third-trimester ultrasound examinations from separate pregnancies in three individual years (1451 in 1985, 3016 in 1988, and 2625 in 1991) were compared. Overall, visualization across all gestational ages improved from 63.9% (1985) to 85.8% (1988) to 87.3% (1991), with the year in which the scan was performed explaining 19.6% of the variance in visualization. Maternal size (as determined by body mass index) remained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
0
7
1
Order By: Relevance
“…Bainco et al [11] showed an increased incidence of abruption among obese women when compared to women with normal BMI. But results of Wolf et al [12] including ours did not show association of increase BMI and APH. 5): In our study, there was no significant association with multiple pregnancy and BMI, which occurred equally in obese group (1.06%) and control group (1%).…”
Section: Gdm (Table 4)contrasting
confidence: 68%
See 1 more Smart Citation
“…Bainco et al [11] showed an increased incidence of abruption among obese women when compared to women with normal BMI. But results of Wolf et al [12] including ours did not show association of increase BMI and APH. 5): In our study, there was no significant association with multiple pregnancy and BMI, which occurred equally in obese group (1.06%) and control group (1%).…”
Section: Gdm (Table 4)contrasting
confidence: 68%
“…APGAR at 5 min: The difference of Apgar at 5 minutes between obese and control group was statistically significant. This is conflicting with study done by Myles et al [19] and Wolf et al [12].…”
Section: Fetal Outcomementioning
confidence: 66%
“…Attenuation encompasses absorption, reflection, reverberation and scatter 37 . The overall visualization of fetal organs with respect to F o r P e e r R e v i e w Obstetrical ultrasound and obesity increasing maternal size has been previously addressed by several studies 38,39 . Reduction in successful image generation was most marked for cardiac and cerebrospinal structures as well as the umbilical cord 40,41 .…”
Section: Image Claritymentioning
confidence: 99%
“…Attenuation results from absorption, reflection, reverberation, and scatter 37. The visualization of fetal organs with respect to increasing maternal size has been previously addressed 38, 39. Cardiac and cerebrospinal structures as well as the umbilical cord are most affected 40, 41.…”
Section: Obstetric Ultrasoundmentioning
confidence: 99%
“…The accuracy of prenatal screening for malformations would be expected to depend upon the scanning protocol used, and the frequency with which anatomic features of the fetus are visualized during sonography. Past studies have shown that, in the mid-trimester, fetal organ visualization improves with advancing gestational age 5 -7 , is hampered by maternal obesity 6,8 and abdominal wall scarring 9 , and has improved over time and with the introduction of harmonic imaging technology 10,11 .…”
Section: Introductionmentioning
confidence: 99%